Survey of code-based digital signatures - Yongcheng SONG; Xinyi HUANG; Wei WU; Haixia CHEN (网络与信息安全学报)
The rapid development of quantum computing theory and practice brings great uncertainty to the security of cryptography based on hard problems in number theory.Code-based hard problem is recognized as NP-complete problem, the complexity increases exponentially, and there is currently no threat of quantum computing to code-based cryptographic algorithm.Therefore, code-based algorithm can resist the quantum algorithm attack, which is one of the main directions of quantum-resistant cryptography.It is still an open problem to design secure and efficient code-based signatures.For many years, international researchers use classical and new methods to construct code-based signatures, but existing constructions are weak in security or poor in performance.Code-based signatures were comprehensively summarized and analyzed, and future research directions were indicated.